Comparison of Four-Level Modification Triage with Five Level Emergency Severity Index (ESI) Triage Based on Level of Accuracy and Time Triase - Zustantria Agustin Minggawati; Achmad Faried; Ayu Prawesti Priambodo (Jurnal Keperawatan Padjadjaran, 2020)
The triage system currently recommended by the Association of Emergency Physicians (ACEP) and Emergency Nurses Association (ENA) is a five levels triage, Emergency Severity Index (ESI) due to more structured, concise, and clear. Cibabat Hospital used a relatively new triage of four modified levels of the Australian Triage Scale (ATS) which accuracy and time triage have not been evaluated. The purpose of this study was to compare the four level triage of modification of ATS and five levels of ESI triage based on accuracy and time triage. The researcher used a quantitative quasi-experimental design with samples of triage activities totaling 38 in the control group and 38 intervention groups, using accidental sampling techniques. Univariate analysis consisted of frequency distribution for nurse characteristics, time triage and accuracy, bivariate analysis used the Mann-Whitney test. The results showed there were no differences, triage modification of ATS with ESI triage in accuracy (p-0.488), and length of triage (p-0.488) ESI triage accuracy was in the expected triage category (76.3%), under triage (13.2%), and over triage (10.5%). Triage modified ATS, expected triage (73.7%), under triage (18.4%), and over triage (7.9%). ESI triage has more expected and less under triage than ATS modification triage. Under triage caused prolong waiting times, unexpected risks, increases morbidity and mortality. Based on the length of time, ESI triage averaged 167 seconds, triage modification of ATS an average of 183 seconds. ESI flowchrat is easier to understand because is simple, has slight indicators in each category. Conclusion of this study is there is no significant difference in the level of accuracy and duration of triage. However, based on data distribution, ESI triage gives more expected triage decisions, less under triage and 16 seconds faster. Suggestions given to the Cibabat Hospital, can use ESI triage as an alternative triage assessment option because easy to use, structured, simple, and clear.